Spine and Non-spine Bone Metastases – Current Controversies and Future Direction. Issue 11 (November 2020) - Challapalli, A.; Aziz, S.; Khoo, V.; Kumar, A.; Olson, R.; Ashford, R.U.; Gabbar, O.A.; Rai, B.; Bahl, A.
Abstract: Bone is a common site of metastases in advanced cancers. The main symptom is pain, which increases morbidity and reduces quality of life. The treatment of bone metastases needs a multidisciplinary approach, with the main aim of relieving pain and improving quality of life. Apart from systemic anticancer therapy (hormonal therapy, chemotherapy or immunotherapy), there are several therapeutic options available to achieve palliation, including analgesics, surgery, local radiotherapy, bone-seeking radioisotopes and bone-modifying agents. Long-term use of non-steroidal analgesics and opiates is associated with significant side-effects, and tachyphylaxis. Radiotherapy is effective mainly in localised disease sites. Bone-targeting radionuclides are useful in patients with multiple metastatic lesions. Bone-modifying agents are beneficial in reducing skeletal-related events. This overview focuses on the role of surgery, including minimally invasive treatments, conventional radiotherapy in spinal and non-spinal bone metastases, bone-targeting radionuclides and bone-modifying agents in achieving palliation. We present the clinical data and their associated toxicity. Recent advances are also discussed. Highlights: Bone metastases (BoM) are common in prostate, breast and lung cancers. Treatment of BoM is a multimodal approach, aiming to improve pain and quality of life. Role of surgery, conventional radiotherapy, radionuclides and bone-modifying agents are discussed.